1998
DOI: 10.1002/(sici)1097-0215(19980619)79:3<215::aid-ijc1>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between methylation status of thep16/CDKN2 gene and the expression of p16 and Rb proteins in primary non-small cell lung cancers

Abstract: In order to clarify the frequency of p16 gene inactivation and its relationship with Rb expression, immunohistochemical analysis of p16 and Rb proteins was carried out on 82 paraffin‐embedded sections of primary non‐small cell lung cancers (NSCLCs). From immunohistochemical results, abnormal p16 expression was observed in 66% of NSCLCs, 80% in squamous cell carcinomas and 46% in adenocarcinomas. An inverse correlation between p16 and Rb expressions was noted. Moreover, the methylation status of the p16 gene wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
53
4
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 10 publications
11
53
4
1
Order By: Relevance
“…Changes in the other pocket proteins (p107 and p130) have been detected in only a few cases (Helin et al, 1997). In contrast to SCLC, the majority of NSCLC cases exhibit abnormalities in the upstream regulators of the pRb pathway, including inactivation of p16 (Kashiwabara et al, 1998;Tanaka et al, 1998) through different mechanisms , reduced levels of p27 Kip (Kawana et al, 1998;Yatabe et al, 1998), and enhanced expression of cyclin D1 (Marchetti et al, 1998). It is likely that inactivation of cdk4,6 inhibitors (p16) and overexpression of cyclin D1 bypass the pRb checkpoint, allowing progress through G 1 into DNA synthesis (Driscoll et al, 1997;Shapiro et al, 1998).…”
Section: The Cell-cycle Machinery and Lung Cancermentioning
confidence: 99%
“…Changes in the other pocket proteins (p107 and p130) have been detected in only a few cases (Helin et al, 1997). In contrast to SCLC, the majority of NSCLC cases exhibit abnormalities in the upstream regulators of the pRb pathway, including inactivation of p16 (Kashiwabara et al, 1998;Tanaka et al, 1998) through different mechanisms , reduced levels of p27 Kip (Kawana et al, 1998;Yatabe et al, 1998), and enhanced expression of cyclin D1 (Marchetti et al, 1998). It is likely that inactivation of cdk4,6 inhibitors (p16) and overexpression of cyclin D1 bypass the pRb checkpoint, allowing progress through G 1 into DNA synthesis (Driscoll et al, 1997;Shapiro et al, 1998).…”
Section: The Cell-cycle Machinery and Lung Cancermentioning
confidence: 99%
“…A number of studies have demonstrated frequent methylation in lung cancer cells of several tumor suppressor genes including the DNA repair gene O 6 -methylguanine-DNA methyltransferase (MGMT), 8,9 p16 INK4a , 10,11 ras association domain family 1A (RASSF1A), 12,13 apoptosis-associated genes such as death-associated protein kinase (DAPK), 14 and retinoic acid receptor b (RARb) 15 ; in contrast, methylation of these genes was rare in nonmalignant lung tissue. 9 We previously reported that identification of promoter methylation of these 5 tumor suppressor genes in serum DNA could be useful for early detection of lung cancer.…”
mentioning
confidence: 99%
“…1,2 Several reports indicated that hypermethylation of p16INK4a occurs frequently in non small cell lung cancer (NSCLC). [3][4][5] Belinsky et al 6 even linked p16INK4a hypermethylation to an early stage in the pathogenesis of lung cancer and suggested that p16INK4a hypermethylation in serum DNA may serve as an early diagnostic marker of lung cancer.Environment-epigenetic interactions may play a role in the geographic variation of human cancer incidence. Aberrant hypermethylation in the CpG-rich promoter regions of many tumor suppressor genes was associated with the lack of gene transcription and thus contributed to the formation and progression of lung cancer, such as p16INK4a, DAPK, GSTP1 and MGMT.…”
mentioning
confidence: 99%
“…1,2 Several reports indicated that hypermethylation of p16INK4a occurs frequently in non small cell lung cancer (NSCLC). [3][4][5] Belinsky et al 6 even linked p16INK4a hypermethylation to an early stage in the pathogenesis of lung cancer and suggested that p16INK4a hypermethylation in serum DNA may serve as an early diagnostic marker of lung cancer.…”
mentioning
confidence: 99%